2019
DOI: 10.1155/2019/9072531
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study in China to Determine Whether GPS Data and Derivative Indicator Can Be Used to Identify Risky Drivers

Abstract: This paper presents an investigation of the relationship between driver risk and factors indicating vehicle’s speed and driver’s acceleration behavior. The main objective is to examine whether GPS data and derivative indicator can be used to identify risky drivers by means of factor analysis. In doing so, a real road driving experiment is conducted to collect data. Fifty drivers are asked to drive along a route which includes both rural highways and urban roads. The trajectories are recorded by GPS devices to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The key indicators that influence their accident risk are azimuthal change, acceleration dispersion, and average speed. This relationship has also been consistently found in the research [65,66]. This study confirmed the positive correlation between these three indicators and bus driver accidents.…”
Section: Discussionsupporting
confidence: 88%
“…The key indicators that influence their accident risk are azimuthal change, acceleration dispersion, and average speed. This relationship has also been consistently found in the research [65,66]. This study confirmed the positive correlation between these three indicators and bus driver accidents.…”
Section: Discussionsupporting
confidence: 88%
“…All statistical analyses were conducted using SPSS Statistics software [32]. For the datafitting normal distribution, the analysis of variance (ANOVA) was used for the hypothesis test.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, the lane-changing data are classified into three categories according to the acceleration value of the FV when the SV starts to change lanes to verify the validity of the warning model. That is, the acceleration value of the FV less than −0.5 m/s 2 is used as the hazard perception threshold, and the lane-changing data are classified into the hazardous area [42,43]; data with slight braking (−0.5 < a F ≤ −0.15 m/s 2 ) is classified into the potential conflict area [44]; and data with an acceleration value above −0.15 m/s 2 is considered as safe lane-changing data and is classified into the safety area. The distribution of the acceleration of the FV when the SV starts to change lanes is shown in Figures 15 and 16.…”
Section: Dss =mentioning
confidence: 99%